Does C-reactive protein predict time to recovery and benefit from oseltamivir treatment in primary care patients with influenza-like illness? A randomized controlled trial secondary analysis. (2nd October 2021) - Harbin, Nicolay Jonassen; Rystedt, Karin; Lindbaek, Morten; Radzeviciene, Ruta; Westin, Johan; Gunnarsson, Ronny; Butler, Christopher C.; van der Velden, Alike W.; Verheij, Theo J.; Sundvall, Pär-Daniel
Abstract: Objective: Recovery time and treatment effect of oseltamivir in influenza-like illness (ILI) differs between patient groups. A point-of-care test to better predict ILI duration and identify patients who are most likely to benefit from oseltamivir treatment would aid prescribing decisions in primary care. This study aimed to investigate whether a C-reactive protein (CRP) concentration of ≥30 mg/L can predict (1) ILI disease duration, and (2) which patients are most likely to benefit from oseltamivir treatment. Design: Secondary analysis of randomized controlled trial data. Setting: Primary care in Lithuania, Sweden and Norway during three consecutive influenza seasons 2016–2018. Subjects: A total of 277 ILI patients aged one year or older and symptom duration of ≤72 h. Main outcome measures: Capillary blood CRP concentration at baseline, and ILI recovery time defined as having 'returned to usual daily activity' with residual symptoms minimally interfering. Results: At baseline, 20% (55/277) had CRP concentrations ≥30mg/L (range 0–210). CRP concentration ≥30 mg/L was not associated with recovery time (adjusted hazards ratio (HR) 0.80: 95% CI 0.50–1.3; p  = 0.33). Interaction analysis of CRP concentration ≥30 mg/L and oseltamivir treatment did not identify which patients benefit more from oseltamivir treatment (adjusted HR 0.69: 95% CI 0.37–1.3; p  = 0.23). Conclusion: There was no association between CRP concentration of ≥30 mg/L and recovery time from ILI. Furthermore, CRP could not predict which ILI patients benefit more from oseltamivir treatment. Hence, we do not recommend CRP testing for predicting ILI recovery time or identifying patients who will receive particular benefit from oseltamivir treatment. Key Points: Predicting disease course of influenza-like illness (ILI), and identifying which patients benefit from oseltamivir treatment is a challenge for physicians.  There was no association between CRP concentration at baseline and recovery time in patients consulting with ILI in primary care.  There was no association between CRP concentration at baseline and benefit from oseltamivir treatment.  We, therefore, do not recommend CRP testing for predicting recovery time or in decision-making concerning oseltamivir prescribing in ILI patients.